Participação de espécies reativas na fotodegradação do corante remazol amarelo ouro empregando SrSnO3 ou TiO2 como catalisador - Teixeira, Ana Rita Ferreira Alves (2015)
Heterogeneous photocatalysis is an important alternative for environmental remediation, with the possibility of its use for degradation of textile dyes effluents, as remazol golden yellow (RNL). Many semiconductors can be employed as photocatalysts, highlighting commercial TiO2 P25 Evonik, a mixture of anatase and rutile phases. Other materials have been studied for such application, including SrSnO3. In this work, strontium stannate was synthesized by the modified Pechini method and its photocatalytic activity on the degradation of the RNL textile was evaluated, as well as the activity for the commercial P25. The aim of this study was determining the role of each active specie on the photodegradation of the RNL system. In order to achieve such objective, some experiments were carried out in the presence of hydroxyl radical, hole and electron scavengers (isopropanol, formic acid and silver, respectively). The photocatalysts were characterized by X-ray diffraction (XDR), infrared spectroscopy (IV), Raman spectroscopy, UV-visible spectroscopy, surface area by BET method, and zero charge potential. SrSnO3 obtained showed strontium carbonate as secondary phase, and this may have caused a short-range disorder for the material. The photocatalytic performance was evaluated by UV-Vis spectroscopy analysis of the RNL solutions before and after UVC irradiation in the presence of catalysts. The use of scavengers showed that, for both catalysts, hydroxyl radical play a major role, holes have an important participation on the formation of these radicals while electrons have no considerable participation. The results confirm that recombination is a limiting factor for SrSnO3 and P25.